Use of hepatitis B viremic donors in kidney transplant recipients: A single center experience. Issue 4 (9th July 2022) - Carnemolla, Brooke T.; Kutzler, Heather L.; Kuzaro, Hillary A.; Morgan, Glyn; Serrano, Oscar K.; Ye, Xiaoyi; Cheema, Faiqa
Abstract: Utilization of Hepatitis B virus (HBV)‐infected kidney allografts represents an opportunity to bridge the gap between organ supply and demand. Highly efficacious vaccines and antiviral therapies allow these allografts to be transplanted with negligible risk to the recipient. The purpose of this study was to describe the prophylactic strategies and related clinical outcomes of kidney transplant recipients who received a kidney from an HBV viremic donor. Eight patients received an allograft from an HBV viremic deceased kidney donor between January 1, 2017 and December 4, 2020. All recipients were immune to hepatitis B with a surface antibody titer greater than or equal to 10 mIU/ml (range: 12 ‐ > 1000 mIU/ml). After transplant, 62.5% demonstrated HBV core antibody seroconversion at an average of 47.4 ± 28.5 days post‐transplant. Anti‐viral prophylaxis was initiated in 87.5% of patients; 62.5% preemptively during the transplant admission (range 1–3 days post‐transplant) and 25% following HBcAb seroconversion (range 45–304 days post‐transplant). Of the four patients who were started on entecavir preemptively, two subsequently core converted. These two patients had an HBV surface antibody less than 100 mIU/ml at the time of transplant. None of the recipients converted to HBV surface antigen positivity. The average estimated glomerular filtration rate was 41 ± 19 ml/min/1.73m 2, and there were no significant elevations in liver enzymes through one year post‐transplant. The use of HBV viremic kidney allografts may represent an additional source of transplant organs; however, more studies are needed to better elucidate the optimal protective strategies for these recipients. Abstract :